2013
DOI: 10.1155/2013/932529
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Renal Pelvis Rupture: Unexpected Complication of Urolithiasis Expected to Passage with Observation Therapy

Abstract: Seventy percent of ureteral stones are located at distal ureter. Effective and safe passage of distal ureter stones is mediated by observation or medical expulsive treatment. Most of stones located at distal ureter pass spontaneously under observation; however, some are complicated with urinary tract infection, hydronephrosis, and renal function disturbances. Spontaneous perforation of the upper ureter is a rare condition that poses diagnostic and therapeutic problems. This case is reported, because the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Since hydroureteronephrosis subsided in a short period, conservative treatment was the preferred method of choice in our case, contrary to the tendency for percutaneous nephrostomy at the beginning of the course. Lien et al 10 reported good results and mostly an uneventful recovery with conservative treatment including antibiotics in the presence of a distal ureteric stone with calyceal rupture, as is the case with most of the relevant literature 5,7 .…”
Section: Discussionmentioning
confidence: 94%
“…Since hydroureteronephrosis subsided in a short period, conservative treatment was the preferred method of choice in our case, contrary to the tendency for percutaneous nephrostomy at the beginning of the course. Lien et al 10 reported good results and mostly an uneventful recovery with conservative treatment including antibiotics in the presence of a distal ureteric stone with calyceal rupture, as is the case with most of the relevant literature 5,7 .…”
Section: Discussionmentioning
confidence: 94%
“…On physical examination, peritoneal irritation signs, and the presentation of peritonitis are often responsible for the delayed diagnosis and incorrect treatment [12]. Tuncay et al [13] proposed that pain may not be an early manifestation; when urinary extravasation increases in size to form a urinary cyst, SRRP may present as a lumbar mass in the early stage, once the urinary cyst increases in size until it compresses the ureter or when extravasated urine becomes infected, lumbar pain symptoms will occur. Other symptoms of SRRP include nausea, vomiting, and gross hematuria [14].…”
Section: Discussionmentioning
confidence: 99%
“…Rupture of the renal pelvis caused by hydration has been reported previously. One report documented rupture of the renal pelvis in a patient with a ureteral stone who was being observed while receiving hydration and analgesics ( Tas et al, 2013 ). Another study reported on a woman at 19 weeks' gestation in whom rupture of the renal pelvis occurred after she received a rapid intravenous infusion before cervical cerclage during spinal anesthesia ( Huang et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%